Tabby McTat - Donaldson, Julia; Scheffler, Axel (London : Alison Green Books, 2010)
Tabby McTat enjoys singing for coins with his owner Fred, but when Fred is in an accident and the two get separated, they must try to find each other again.
3.7
K-3.
K-3
Keywords: Cats -- Juvenile fiction; Lost articles -- Juvenile fiction; Street entertainers -- Juvenile fiction; Cats -- Fiction; Lost and found possessions -- Fiction; Stories in rhyme; Street entertainers -- Fiction; Cats -- Fiction; Lost and found possessions -- Fiction; Stories in rhyme; Street entertainers -- Fiction; Picture books for children